Relationship between Glucose-6-Phosphate Dehydrogenase Deficiency, X-Chromosome Inactivation and Inflammatory Markers - Alessandra Errigo; Angela Bitti; Franca Galistu; Roberta Salis; Giovanni Mario Pes; Maria Pina Dore (MDPI AG, 2023)
Recent studies suggest that X-linked glucose-6-phosphate dehydrogenase (G6PD) deficiency entails a proinflammatory state that may increase the risk of several disease conditions. However, it is not clear how this relates to the degree of enzyme insufficiency and, in heterozygous females, to skewed inactivation of the X chromosome. This study aimed to (i) investigate the enzyme activity in a cohort of 232 subjects (54.3% females) from Northern Sardinia, Italy, further stratified into three subgroups (G6PD normal, partial deficiency and total deficiency); (ii) measure the levels of some non-specific inflammatory markers, such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and those derived from cell counts, such as neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) and platelet-to-lymphocyte ratio (PLR), in relation to the underlying molecular defect and X inactivation. G6PD activity was measured in red blood cells according to G6PD/6PGD ratio, and X-chromosome inactivation was assessed by the HUMARA method. Overall, ESR was increased in males with total deficiency compared with normal males (15.0 ± 7.2 vs. 11.9 ± 6.2, p = 0.002, Tukey's test), albeit not in males with partial deficiency. High-sensitivity CRP was slightly increased in males with total deficiency, compared to males with normal G6PD activity (5.96 ± 3.39 vs. 3.95 ± 2.96, p = 0.048). In females, neither marker showed significant differences across the subgroups. MLR was significantly and progressively increased from normal to totally deficient subjects with intermediate values in partially deficient subjects (0.18, 0.31 and 0.37, ANOVA p = 0.008). The NLR and PLR were not different in the three subgroups. Our findings show that G6PD deficiency may be associated with a proinflammatory profile, especially in elderly females, and worsened by the concomitant asymmetric inactivation of the X chromosome.